Transcriptome Analysis of Effect of Cordyceps militaris Aqueous Extract in Human Gastric Cancer Cell BGC-823 on Different RCD Pathways - Mingqi CUI; Kaiwen YU; Yang SONG; Fangxu XU; Shenghou WANG; Ze WANG (Shipin gongye ke-ji)
Objective: The main regulated cell death (RCD) signaling pathway of Cordyceps militaris (XG) water extract that affects the growth activity of the human gastric cancer cell line BGC-823 was analyzed and predicted using transcriptome sequencing technology. Methods: The effect of XG aqueous extract on the proliferation of gastric cancer cells was determined using the MTT method. Transcriptome analysis revealed significant differentially expressed genes (DEGs) and their Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, resulting in the identification of 10 hub genes involved in the apoptosis, autophagy, necroptosis, and ferroptosis signaling pathways. Laser confocal microscopy, flow cytometry, and quantitative real time polymerase chain reaction (qRT-PCR) were employed to further validate the induction of apoptosis in gastric cancer cells by the XG aqueous extract. Results: The inhibitory effect of XG water extract on the growth of the human gastric cancer cell line BGC-823 was dose-dependent. A total of 5885 differentially expressed genes were identified through transcriptome sequencing analysis, with significant enrichment in the apoptosis (P=0.001) and autophagy (P=0.008) signaling pathways. In addition to ferroptosis, the expression levels of hub genes associated with other signaling pathways were significantly inhibited, including the key factor of caspase-dependent apoptosis (CASP3, CASP9, CASP7, APAF1) as well as ULK1, ULK2, UVRAG, Atg14, and Atg5 related to autophagosome formation. Cytological examination revealed typical apoptotic morphological characteristics in gastric cancer cells treated with the XG water extract, with an early apoptotic rate reaching 24.8%, while cell cycle arrest occurred at the G2/M stage. qRT-PCR showed that the expression of BCL2, BCL2L1, CASP3, CASP9, and XIAP was significantly inhibited (P<0.01), whereas that of ENDOG and AIF was significantly upregulated (P<0.01), consistent with the results of transcriptome sequencing. Conclusion: C. militaris primarily inhibits the growth of the human gastric cancer cell line BGC-823 through a caspase-independent mitochondrial apoptosis pathway while also influencing the activation of autophagy and other signaling pathways. These findings provide theoretical support for using C. militaris in functional foods.